1959
DOI: 10.1071/bi9590072
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Natal Development of Skin and hair in Cattle (Bos Taurus L.)

Abstract: A histological study has been made of the development of the skin and hair follicles in 33 foetuses, ranging in age from 68 to 274 days, and seven new-born specimens, of various breeds of Bos taurus L. Skin samples were taken from the mid-lateral region of the trunk, and both serial sections and whole mount preparations have been examined. Extensive use has been made of' counts of the follicle and hair population as well as skin and hair follicle measurements which hitherto have apparently received little att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

1960
1960
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
19
0
4
Order By: Relevance
“…However, the seemingly conflicting data beco'mes more understandable when the effects of breed, sex, and age are considered with the data reported. Lyne & Heideman (1959) reported that the density of all hair follicles in cattle are established at birth, and Turner et al (1962) reported that the total number of follicles on Bos taurus beef cattle was constant. Cattle age has been shown to have a significant influence on hair density up to 3 years (Carter & Dowling, 1954), and Turner et al (1962) concluded that the density of hairs was higher in male than in female calves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the seemingly conflicting data beco'mes more understandable when the effects of breed, sex, and age are considered with the data reported. Lyne & Heideman (1959) reported that the density of all hair follicles in cattle are established at birth, and Turner et al (1962) reported that the total number of follicles on Bos taurus beef cattle was constant. Cattle age has been shown to have a significant influence on hair density up to 3 years (Carter & Dowling, 1954), and Turner et al (1962) concluded that the density of hairs was higher in male than in female calves.…”
Section: Discussionmentioning
confidence: 99%
“…When a loose mass of feltable animal fibers is agitated in water with some pressure on them, the individual fibers more preferentially in one direction (the directional fiber effect) becoming entangled and consolidating the structure of the assembly. The product is a natural or pressed felt (MAKINSON, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The full complement of hair follicles is presented at c . 200 days of gestation and all follicles are mature at birth . Because there were approximately 50% of hair follicles missing without any signs of their presence in the past, we think that hypotrichosis in this case is of congenital origin.…”
Section: Discussionmentioning
confidence: 99%